Optimization of Roll Configuration and Investigation of Forming Process in Three-Roll Planetary Rolling of Stainless Steel Seamless Tubes - Chuanchuan Ma; Tuo Li; Chun Xue; Ri Jin; Zhibing Chu; Meirong Shuai; Leifeng Tuo (Metals)
Three-roll planetary rolling technology has emerged as a primary method for manufacturing seamless tubes due to its advantages, including significant single-pass deformation, low energy consumption, and the ability to continuously roll long workpieces. Based on the forming characteristics of three-roll planetary rolling, this study established a simulation model of the rolling process, which includes key parameters such as the friction coefficient, roll speed, and roll deflection angle. Using finite element software, the effects of these parameters on the rolling process are simulated and analyzed. By comparing critical indicators such as the equivalent stress, rolling temperature, and roundness of the workpiece, the influence of the process parameters on the forming quality of three-roll planetary rolling is revealed. The optimal parameter combination is determined as follows: a friction coefficient of 0.3, roll speed of 120 rpm, and roll deflection angle of 9°. This research provides a reliable theoretical foundation for subsequent roll profile design and process parameter optimization in three-roll planetary rolling.